2010
DOI: 10.1111/j.1365-2710.2009.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone reduces postoperative nausea in total knee and hip arthroplasty

Abstract: In total knee and hip arthroplasty, methylprednisolone is effective in preventing postoperative nausea; however, higher doses of methylprednisolone may be needed to prevent vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
3
18
0
1
Order By: Relevance
“…Our findings agree with those of previous small series [15,36,38,40] and reviews of numerous perioperative settings [19,21,22,46] that found no association between corticosteroid use and increased risk for postoperative wound infection. Furthermore, studies using higher corticosteroid doses than that used in our study showed no increase in postoperative wound infection after major orthopaedic surgeries [1,5,19,25,46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings agree with those of previous small series [15,36,38,40] and reviews of numerous perioperative settings [19,21,22,46] that found no association between corticosteroid use and increased risk for postoperative wound infection. Furthermore, studies using higher corticosteroid doses than that used in our study showed no increase in postoperative wound infection after major orthopaedic surgeries [1,5,19,25,46].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that perioperative use of single, lowdose corticosteroids significantly decreased inflammatory markers after TKA [23,24,49]. However, despite the potential benefits and reported efficacy in numerous surgical procedures, only a few small studies involving less than 25 patients per group evaluated the efficacy and safety of corticosteroids after TKA [15,24,38,40]. Moreover, heterogeneity among studies regarding type, dosage, and administration protocol of corticosteroids and concomitant pain control regime make it difficult to judge the practical value of corticosteroid use after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…6 Methylprednisolone, the steroid administered to patients in the 2 groups in this study, has been shown to decrease late PONV extending to 24 hours and beyond. 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…A cohort study employing an equivalent dose of methylprednisolone in patients undergoing total hip and knee surgery reported a statistically significant reduction in nausea and prevention of vomiting, supporting our notion that dexamethasone is most likely the most effective glucocorticoid used to prevent PONV. 25 …”
Section: Pro: Dexamethasone Anaesthesiologic Point Of Viewmentioning
confidence: 99%